2000
DOI: 10.1164/ajrccm.161.5.9909024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atenolol, Amlodipine, Enalapril, Hydrochlorothiazide, and Losartan for Antihypertensive Treatment in Patients with Obstructive Sleep Apnea

Abstract: We compared the effects of atenolol (50 mg), amlodipine (5 mg), enalapril (20 mg), hydrochlorothiazide (25 mg), and losartan (50 mg) given in once-daily oral doses on office and ambulatory blood pressures (BPs) in patients with hypertension and obstructive sleep apnea (OSA). Each of 40 randomized patients was treated in sequence with two of the five agents (balanced incomplete block design). Treatment periods lasted 6 wk and were separated by a 3-wk washout period. Changes in BP from baseline with the study su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 25 publications
2
82
0
8
Order By: Relevance
“…200,201 Hence, decreased intravascular volume and attenuated venous congestion resulting from heart failure treatment could potentially reduce OSA severity. However, there is no systematic evidence that specific drugs used to treat heart failure have any direct influence on the severity of OSA, 169 apart from an increase in AHI reported in the setting of cough and airway inflammation with angiotensin-converting enzyme inhibitors. 170 …”
Section: Osa and The Origin And Progression Of Heart Failurementioning
confidence: 99%
“…200,201 Hence, decreased intravascular volume and attenuated venous congestion resulting from heart failure treatment could potentially reduce OSA severity. However, there is no systematic evidence that specific drugs used to treat heart failure have any direct influence on the severity of OSA, 169 apart from an increase in AHI reported in the setting of cough and airway inflammation with angiotensin-converting enzyme inhibitors. 170 …”
Section: Osa and The Origin And Progression Of Heart Failurementioning
confidence: 99%
“…Studies also suggest an increase in the risk of myocardial infarction and stroke in untreated OSAHS (Good et al, 1996;Leung et al, 2001;Leung, 2009), Bblockers have been reported to be the most effective among antihypertensive agents, in lowering daytime BP in hypertensive OSA patients as sympathetic overactivity is involved. However antihypertensive medications have little effect on nocturnal BP in OSA, possibly because they do not reduce OSA (Kraiczi et al, 2000). Stress hormones may be triggered by frequent decrease in blood oxygen levels (Crummy et al, 2008) and can increase heart rate and worsen the heart failure.…”
Section: Associated Featuresmentioning
confidence: 99%
“…Another report showed significant reduction of the nocturnal systolic and diastolic BP levels following treatment with b blockers compared with Ca antagonists, ACE inhibitors and angiotensin receptor blockers, although there was no significant difference in the degree of reduction of daytime BP during awakening, nor any difference compared with diuretics. 34 However, one study suggested that nocturnal BP level could only be minimally controlled by single drug administration, including b blockers, although daytime BP levels could be reduced. 35 Thus, no consensus has yet been established on the OSAS-specific efficacy of b-blockers.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%